APPLICATION OF SUPPLY CHAIN MANAGEMENT PROCESS ON BUSINESS PERFORMANCE (Case Study on Roti-Qu bakery in Batang) - Utami, Anindya Putri; Kusumawardhani, Amie (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Competitiveness in the field of production and service is very visible with many companies flocking to create a product with new innovations so as to produce effective and efficient products by paying attention to the company's supply chain flow. Roti-Qu in Batang is one of the companies in the form of a CV business entity that produces bread which has produced 50 branches spread over 400 employees, this company is well aware of supply chain management. This study uses a qualitative approach, with data collection through field observations, interviews and documentation. With regard to research on supply chain management, this research was conducted on the object of a bakery, namely Roti-Qu in Batang Regency, precisely in Sambong Village with the research subject being the owner of Roti-Qu, the Procurement Section / Warehouse of Roti-Qu and the Production Division of Roti-Qu. In the application of supply chain management, it was found that the relationship with the supplier had a positive and significant influence on the material flow because the owner and the warehouse department were able to solve the problems that occurred. Relationships with customers are considered to have a positive effect on material flow. Sharing information looks very risky on any information obtained by each division. However, it was found that information sharing had a positive effect on material flow because, according to a statement from the warehouse and production, Roti-Qu solved the problem by reconfirming the material orders needed by the warehouse, production and even branches. Communicate all problems in detail. With the smooth flow of materials influenced by supplier relationships, customer relations and information sharing have a positive impact on business performance at Roti-Qu. Business performance is seen from financial and non-financial perspectives. The results showed that it had a positive effect on job satisfaction. However, for financial business performance, fluctuating sales were found due to the Covid-19 pandemic. The policy implication in this research is that the procurement department handles the supply chain quite well but still requires trust in overcoming recurring problems, business people must make the latest innovations to develop the company, make good use of marketing media, place warehouses closer to areas full of branches. Roti-Qu, job satisfaction is quite good but still requires openness. Keywords : Supply Chain Management, Relationships with suppliers, Relationships with customers, Information sharing, Business performance